EVALUASI KESEIMBANGAN AIR DI PROVINSI JAWA TENGAH - Nugroho, Sutopo Purwo (Center for Environmental Technology, 2007)
Water supply for the domestics use of Central Java Province has been experiencing problems and challenging. With population of 35 million or 16% of Indonesia, it place the province as the third in national population. It have consequently, water need in the province is as such for use of domestics, irrigation/agriculture, industry, etc. Several counties within the province has experiencing water shortage. Particularly during dry season, defisits is inclining that results water use conflicts. Furthermore, conflicts occur not only in counties with water shortage but also in county with sufficient water supply. Conflict is generally triggered by weak management and allocation. This is a result of unlimited territorial sovereighnity of water resources and uncertainty of water rights. Unlimited territorial sovereighnity of water resource contain exclusive right to utilize tap water within the territorial right, in way that the territory hold the sole right to exploit the resource without compensation to neighbouring territory. Hence, water balance should be investigated better and comprehensively.Ã‚Â Kata kunci: keseimbangan air, konflik, sumber daya air, Jawa Tengah.